2016
DOI: 10.1159/000453068
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Mast Cell-Nerve Association and Neuropeptide Receptor Expression on Mast Cells in Perennial Allergic Rhinitis

Abstract: Objectives: Mast cells (MCs) and nerves play an important role in allergic rhinitis (AR), but little is known about their crosstalk in AR. The aim of this study was to investigate MC-nerve interaction in the human nasal mucosa during AR. Methods: The association between MCs and nerves, the expression of neuropeptide receptors (neurokinin 1 receptor [NK1R], neurokinin 2 receptor [NK2R], calcitonin gene-related peptide receptor [CGRPR], and MrgX2) on MCs, and protease-activated receptor 2 (PAR2) and tyrosine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…Airway vagal sensory neurons play a pivotal role in the neurogenic inflammation of the airways [11] via neuronal reflex and by triggering the release of a variety of neuropeptides [29]. We showed here that the increased DC/neuron ratio in the OVA compared to the saline groups was identical in this OVA model as in the house dust mite model previously reported [11].…”
Section: Discussionsupporting
confidence: 77%
“…Airway vagal sensory neurons play a pivotal role in the neurogenic inflammation of the airways [11] via neuronal reflex and by triggering the release of a variety of neuropeptides [29]. We showed here that the increased DC/neuron ratio in the OVA compared to the saline groups was identical in this OVA model as in the house dust mite model previously reported [11].…”
Section: Discussionsupporting
confidence: 77%
“…Early studies using NK‐1R KO mice showed that the neurokinin receptor‐1 (NK‐1R) was necessary to induce MC‐dependent edema formation . Its expression was inducible in cultured BMMC by IL4 and SCF or in nasal mucosa MC during allergic rhinitis, which may be relevant in inflammatory conditions . Interestingly, new studies found that SP also interacts with MRGPRX2 albeit with somewhat lower affinity (0.5 nM vs 100 nM) and much lower affinity (50 μM) in the case of mouse MRGPRB2 .…”
Section: G‐protein‐coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Human skin mast cells express the G‐protein coupled receptor (GPCR) mas‐related gene X2 (MrgX2) that allows them to be activated for degranulation by polybasic substances, such as compound 48/80 and poly‐L‐lysine . Mast cells also express neuropeptide receptors, such as neurokinin 1 and 2 receptors (NK1R and NK2R), calcitonin gene‐related peptide receptor (CGRPR), and the neurotrophin receptors, tropomyosin‐related kinase A (TrkA), TrkB, and TrkC . Neuropeptides such as substance P, vasoactive intestinal peptide (VIP), and somatostatin, but not eledoisin, physalaemin, neurokinin A, neurokinin B, calcitonin gene‐related peptide (CGRP) stimulate both mast cell degranulation and cytokine production .…”
Section: Introductionmentioning
confidence: 99%